빛과 전기 개념의 연계성에 관한 과학과 교육과정의 국제 비교 - 이효녕, 박병열, 전재돈, 이현동 (교과교육학연구, 2016)
이 연구의 목적은 우리나라를 포함한 7개국의 과학과 교육과정의 연계성을 ‘빛’과 ‘전기’개념을 중심으로 분석하여현재 2009 개정 교육과정에서의 우리나라 과학과 교육과정의 연계성에 대한 문제점을 도출하고 앞으로의 교육과정에서 연계성을 강화하는 일반화 방안을 도출하고자 하였다. 연구 대상은 국가교육과정정보센터(NCIC)에서 수집한 각 나라의 교육과정 원문 및 번역본이며, Tyler(1949)의 교육과정 조직 원리를 바탕으로 종적·횡적 연계성을 기초로 과학과 교육과정 내의‘빛’과 ‘전기’개념에 대한 내용을 비교 분석하였다. 그 결과, 국제적으로 교육과정의 학년 간, 그리고 교과 간 연계의 강화를위해 ‘빛’과 ‘전기’에 대한 중요 개념을 큰 개념으로 설정하고, 저학년부터 고학년까지 나선형 교육과정을 토대로 개념의 반복학습을 이루어나가지만 주변 생활과 현상에 대한 내용에서부터 과학적 개념의 추상적인 원리로 점차 확장되어 가는 것을볼 수 있었다. 우리나라도 나선형 교육과정을 바탕으로 점차 학습 내용을 심화해 나가고 있지만 본 연구에서 분석한 비교 국가들에 비해 내용의 범위와 수준이 성취 기준에 명확히 제시되지 못하고 다른 단원과의 횡적 연계성도 낮음을 볼 수 있었다. 앞으로의 우리나라 교육과정을 새롭게 구성함에 있어서는 주요 개념을 중심으로 연계성을 강화하는 큰 틀이 필요하며 나아가 교육과정을 구성하는 전문가, 교사, 학부모, 학생의 요구를 충분히 반영하여 교육과정을 구성하는 것이 중요하다. The purpose of this study is to derive suggestions and implications to strengthen the science curriculum articulation of Korea through comparative analysis with focus on the articulation of science curriculum concerning the ‘light’ and ‘electricity’ concepts in seven countries. National science curriculum of each country complied from NCIC comparatively analyzed the concept of ‘light’, and ‘electricity’ based on Tyler’s curriculum organizing principle(1949) that is vertical, and lateral connectivity. As a result, the concepts of big idea about ‘light’ and ‘electricity’ was utilized internationally to strengthen the linkage between grades and subjects. As students advance to higher grades, their learned concepts repetition based on the spiral curriculum and concepts expand from simple phenomenon to complicated and discrete theorem. In Korean science curriculum that learning standard was not clear on the range of teaching concepts and level. In addition, lateral connectivity was less compared to other countries. In addition, Korean science curriculum requires appropriate tools to strengthen curriculum linkage and when configuring the science curriculum, reflect demand of curriculum experts, teachers, students and parents. KCI Citation Count: 3